Safety and immunogenicity of intramuscularly administered CS6 subunit vaccine with a modified heat-labile enterotoxin from enterotoxigenic Escherichia coli. Issue 39 (15th September 2021) - Lee, Tida; Gutiérrez, Ramiro L.; Maciel, Milton; Poole, Steven; Testa, Kayla J.; Trop, Stefanie; Duplessis, Christopher; Lane, Alison; Riddle, Mark S.; Hamer, Melinda; Alcala, Ashley; Prouty, Michael; et al.
Abstract: Introduction: Enterotoxigenic Escherichia coli (ETEC) is a common cause of infectious diarrhoea and a leading cause of morbidity and mortality in children living in resource-limited settings. It is also the leading cause of travellers' diarrhoea among civilian and military travellers. Its dual importance in global public health and travel medicine highlights the need for an effective vaccine. ETEC express colonization factors (CFs) that mediate adherence to the small intestine. An epidemiologically prevalent CF is coli surface antigen 6 (CS6). We assessed the safety and immunogenicity of a CS6-targeted candidate vaccine, CssBA, co-administered intramuscularly with the double-mutant heat-labile enterotoxin, dmLT [LT(R192G/L211A)]. Methods: This was an open-label trial. Fifty subjects received three intramuscular injections (Days 1, 22 and 43) of CssBA alone (5 µg), dmLT alone (0.1 µg) or CssBA (5, 15, 45 µg) + dmLT (0.1 and 0.5 µg). Subjects were actively monitored for adverse events for 28 days following the third vaccination. Antibody responses (IgG and IgA) were characterized in the serum and from lymphocyte supernatants (ALS) to CS6 and the native ETEC heat labile enterotoxin, LT. Results: Across all dose cohorts, the vaccine was safe and well-tolerated with no vaccine-related severe or serious adverse events. Among vaccine-related adverse events, a majority (98%) were mild with 79% being short-lived vaccine site reactions. Robust antibody responses were induced in a dose-dependent manner with a clear dmLT adjuvant effect. Response rates in subjects receiving 45 µg CssBA and 0.5 µg dmLT ranged from 50 to 100% across assays. Conclusion: This is the first study to demonstrate the safety and immunogenicity of CssBA and/or dmLT administered intramuscularly. Co-administration of the two components induced robust immune responses to CS6 and LT, paving the way for future studies to evaluate the efficacy of this vaccine target and development of a multivalent, subunit ETEC vaccine.